Treatment of Recurrent Painful Ophthalmoplegic Neuropathy: A Case Where Pregabalin Was Successfully Employed - Laura N. Zamproni; Reinaldo T. Ribeiro; Marina Cardeal (Case Reports in Neurological Medicine)
Recurrent painful ophthalmoplegic neuropathy, previously known as ophthalmoplegic migraine, is a rare condition that affects children and young adults. Its cause and classification are still controversial and, consequently, there are no published treatment guidelines or consensus. Glucocorticoids seem to be beneficial for some patients, but there is no established treatment when failure of this therapy occurs. The aim of this study was to report a case where pregabalin was successfully used after failure of glucocorticoid therapy in a patient with recurrent painful ophthalmoplegic neuropathy.